Fostering Community Environmental Awareness Attitudes through Tuban Mangrove Center Foundation Program - Dwi Wahyu Kartikasari; Kokom Komalasari; Susan Fitriasari (Journal of International Conference Proceedings (JICP), 2020)
The purpose of this research is to know the attitude of environmental awareness conducted by Mangrove Center. This research is based on the high environmental damage in Tuban City. According to the law number 32-year 2009, society has right in managing the environment both independent and organizational. One of the organizations involved in the environment is Mangrove Center Foundation Tuban which is empowers the surrounding society to participate in environmental management. This research uses qualitative methods and with case study design. According to the research, it is obtained data that the attitude of environmental awareness in the society can be formed and grown through the provision of environmental management, such as: concerned with the cleanliness of the environment, tree-planting, management of natural tourism sector, etc.